Acute myeloid leukaemia presenting as faecal incontinence. Issue 5 (23rd April 2007) - Lim, Hoon; Cho, Young Soon; Jang, Pyung Moon; Jung Kim, Ho; Young Jang, Hye
Abstract : Epidural sacral nerve compression as an initial feature of leukaemia is a rare complication. The findings in a 16-year-old boy who presented to an emergency department with symptoms of faecal incontinence are reported herein. Radiological imaging demonstrated soft-tissue masses in the sacral epidural space. The diagnosis of acute myeloid leukaemia was confirmed on bone marrow aspirate. The characteristics and management of extramedullary leukaemia are discussed.